2021
DOI: 10.3390/universe7120489
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Magnetospheres around Herbig Ae/Be Stars

Abstract: We describe four different approaches for the detection of magnetospheric accretion among Herbig Ae/Be stars with accretion disks. Studies of several unique objects have been carried out. One of the objects is the Herbig Ae star HD 101412 with a comparatively strong magnetic field. The second is the early-type Herbig B6e star HD 259431. The existence of a magnetosphere in these objects was not recognized earlier. In both cases, a periodicity in the variation of some line parameters, originating near the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Since the magnetic axis may not align with the rotational axis of the star, the geometry within the magnetosphere is not axisymmetric, leading to a spherical azimuthal inhomogeneity in the circumstellar environment around the star. Consequently, the star's rotation induces cyclic variability in the system, with a periodicity of either the rotational period (Prot$$ {P}_{\mathrm{rot}} $$) or half of it, depending on the visibility of one or both magnetic poles during a rotation period ( P ) (Pogodin et al 2021). Two main types of inhomogeneity contribute to generating this variability: (1) an asymmetric accretion stream inside the magnetosphere relative to the rotation axis and (2) a hot spot on the stellar surface where the accreted material impacts.…”
Section: Photometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the magnetic axis may not align with the rotational axis of the star, the geometry within the magnetosphere is not axisymmetric, leading to a spherical azimuthal inhomogeneity in the circumstellar environment around the star. Consequently, the star's rotation induces cyclic variability in the system, with a periodicity of either the rotational period (Prot$$ {P}_{\mathrm{rot}} $$) or half of it, depending on the visibility of one or both magnetic poles during a rotation period ( P ) (Pogodin et al 2021). Two main types of inhomogeneity contribute to generating this variability: (1) an asymmetric accretion stream inside the magnetosphere relative to the rotation axis and (2) a hot spot on the stellar surface where the accreted material impacts.…”
Section: Photometric Analysismentioning
confidence: 99%
“…Two main types of inhomogeneity contribute to generating this variability: (1) an asymmetric accretion stream inside the magnetosphere relative to the rotation axis and (2) a hot spot on the stellar surface where the accreted material impacts. Spectroscopy of lines originating near the disk/star interaction region can reveal the first item, while the second one can be identified through precise photometry and high‐resolution spectroscopy, particularly using atmospheric lines sensitive to temperature (Pogodin et al 2021). Recently, a similar mechanism is also proposed for classical Be stars in Balona & Ozuyar (2021), where 441 stars are analyzed and it is revealed that such a mechanism shapes the periodogram of the star.…”
Section: Photometric Analysismentioning
confidence: 99%
“…The stellar magnetosphere therefore controls the exchange of mass and angular momentum between the star and the inner disk via the process of magnetospheric accretion (Hartmann et al 2016). This mechanism may also be operating in some higher-mass YSOs (for which the detection of magnetic fields is less common; e.g., Alecian et al 2013;Villebrun et al 2019), as suggested by the observation of rotationally modulated line emission signatures (e.g., Pogodin et al 2021;Brittain et al 2023) characteristic of magnetospheric accretion streams (e.g., Kurosawa et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Рентгеновское излучение этих объектов может формироваться в результате аккреции вещества околозвездного диска [4]. Известны многочисленные свидетельства магнитосферной аккреции среди магнитных звезд Хербига с аккреционными дисками [5]. Недавно опубликовано большое количество параметров звезд Хербига, основанное на данных нового обзора GAIA EDR3 [6].…”
unclassified